Development of a 3D radial MR Imaging sequence to be used for (self) navigation during the scanning of the fetal brain in utero - Morgan, Leah (Department of Human Biology, 2017)
Imaging the fetal brain in utero is challenging due to the unpredictable motion of the fetus. Although ultra-fast MRI sequences are able to image a 2D slice in under a second, thus limiting the time in which fetal motion can corrupt images, Cartesian sampling makes these sequences sensitive to signal misregistration and motion-corruption. Corruption of a single 2D slice renders it impossible to reconstruct 3D volumes from these slices without complex slice-to-volume registration. There is a need for motion-robust sequences that can produce high-resolution 3D volumes of the fetal brain. The Siemens Cardiovascular sequence was edited to produce a new radial readout that sampled a 3D spherical volume of k-space with successive diametric spokes. The diameter end points map a spiral trajectory on the surface of a sphere. The trajectory was modified so that multiple sub-volumes of data are sampled during a single acquisition where M is the number of sub-spirals and N is the number of diametric spokes per sub-spiral. This allows reconstruction of individual sub-volumes of data to produce a series of low-resolution navigator images that can be co-registered to provide information on motion during the acquisition. In this way, a segmented sequence suited to self-navigation was developed. Imaging parameters for the 3D radial sequence were optimised based on theoretical calculations and scans performed in adult brains and abdomens. Optimum values for M and N needed to be determined. Increasing M for a constant total number of projections improves the temporal accuracy of motion tracking at the expense of decreased signal to noise ratio in the navigator images. The effects of breathing and rigid body motion on image quality were also compared between 3D radial and equivalent 3D Cartesian acquisitions. Custom reconstruction code was written to separate the incoming scan data according to the sub-spiral trajectories described within the sequence such that individual navigator images could be reconstructed. Successive sub-spiral images were co-registered to the first navigator image to quantify motion during the acquisition. The resulting transformation matrices were then applied to each sub-spiral image after reconstruction and co-registered sub-spiral images combined in image space to generate the final 3D volume. To improve the quality of navigator images, a method is presented to perform navigator image reconstruction at a lower base resolution, thus reducing streaking artifacts and improving the accuracy of image co-registrations. Finally, the methods developed were applied to two fetal scans. The radial sequence was shown to be more motion-robust than an equivalent Cartesian sequence. The minimum number of diametric spokes that provided navigator images that could be accurately co-registered when scanning an adult brain was N=256, which could be acquired in 1.25 s. For abdominal scans, the minimum number of spokes was N=1024, which could be acquired in about 6 s when water excitation is applied. However, the latter could potentially be reduced by reconstructing navigator images at a lower base resolution. Although fetal scans demonstrated poor image contrast, navigator images were able to track motion during the acquisition demonstrating the potential use of this method for self-navigation. In conclusion, a motion-robust radial sequence is presented with potential applications for prospective navigation during fetal MRI.